Solve for t
t=4
t=0
Share
Copied to clipboard
2t-t=0.25t^{2}
Subtract t from both sides.
t=0.25t^{2}
Combine 2t and -t to get t.
t-0.25t^{2}=0
Subtract 0.25t^{2} from both sides.
t\left(1-0.25t\right)=0
Factor out t.
t=0 t=4
To find equation solutions, solve t=0 and 1-\frac{t}{4}=0.
2t-t=0.25t^{2}
Subtract t from both sides.
t=0.25t^{2}
Combine 2t and -t to get t.
t-0.25t^{2}=0
Subtract 0.25t^{2} from both sides.
-0.25t^{2}+t=0
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
t=\frac{-1±\sqrt{1^{2}}}{2\left(-0.25\right)}
This equation is in standard form: ax^{2}+bx+c=0. Substitute -0.25 for a, 1 for b, and 0 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
t=\frac{-1±1}{2\left(-0.25\right)}
Take the square root of 1^{2}.
t=\frac{-1±1}{-0.5}
Multiply 2 times -0.25.
t=\frac{0}{-0.5}
Now solve the equation t=\frac{-1±1}{-0.5} when ± is plus. Add -1 to 1.
t=0
Divide 0 by -0.5 by multiplying 0 by the reciprocal of -0.5.
t=-\frac{2}{-0.5}
Now solve the equation t=\frac{-1±1}{-0.5} when ± is minus. Subtract 1 from -1.
t=4
Divide -2 by -0.5 by multiplying -2 by the reciprocal of -0.5.
t=0 t=4
The equation is now solved.
2t-t=0.25t^{2}
Subtract t from both sides.
t=0.25t^{2}
Combine 2t and -t to get t.
t-0.25t^{2}=0
Subtract 0.25t^{2} from both sides.
-0.25t^{2}+t=0
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^{2}+bx=c.
\frac{-0.25t^{2}+t}{-0.25}=\frac{0}{-0.25}
Multiply both sides by -4.
t^{2}+\frac{1}{-0.25}t=\frac{0}{-0.25}
Dividing by -0.25 undoes the multiplication by -0.25.
t^{2}-4t=\frac{0}{-0.25}
Divide 1 by -0.25 by multiplying 1 by the reciprocal of -0.25.
t^{2}-4t=0
Divide 0 by -0.25 by multiplying 0 by the reciprocal of -0.25.
t^{2}-4t+\left(-2\right)^{2}=\left(-2\right)^{2}
Divide -4, the coefficient of the x term, by 2 to get -2. Then add the square of -2 to both sides of the equation. This step makes the left hand side of the equation a perfect square.
t^{2}-4t+4=4
Square -2.
\left(t-2\right)^{2}=4
Factor t^{2}-4t+4. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(t-2\right)^{2}}=\sqrt{4}
Take the square root of both sides of the equation.
t-2=2 t-2=-2
Simplify.
t=4 t=0
Add 2 to both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}